A new species of Genkalia (Bacillariophyta) from mountain lakes within the Sichuan Province of China - Luo, F.; You, Q-M.; Wang, Q-X. (Phytotaxa, 2018)
A new diatom species, Genkalia alpina sp. nov., was identified in high elevation lakes in the Mugecuo Scenic Area within the Sichuan Province of China. The area is located in the northern foot of the Hengduan Mountains between the western edge of the Sichuan Basin and the Qinghai-Tibet Plateau, belongs to the subtropical humid monsoon climate, at an altitude of 2600–3800m, with lake water originating mostly from the melting mountain snow. Light and scanning electron microscopy revealed that G. alpina valves are linear with two undulated margins and apices that are subcapitate in larger specimens, but slightly shorter in smaller specimens. The central area is elliptical, and the external proximal raphe ends are straight, or slightly deflected towards the primary valve side. Terminal raphe fissures are strongly bent towards the secondary side and they extend to mantle. Uniseriate striae continue uninterrupted from the valve face to the mantle. The present study is the first report of Genkalia species in China, and expands the geographical distribution of the genus, as well as the known diatom diversity of China.